2012
DOI: 10.1002/9780470559277.ch120125
|View full text |Cite
|
Sign up to set email alerts
|

Specificity Profiling of Protein‐Binding Domains Using One‐Bead‐One‐Compound Peptide Libraries

Abstract: One‐bead‐one‐compound (OBOC) libraries consist of structurally related compounds (e.g., peptides) covalently attached to a solid support, with each resin bead carrying a unique compound. OBOC libraries of high structural diversity can be rapidly synthesized and screened without the need for any special equipment, and therefore can be employed in any chemical or biochemical laboratory. OBOC peptide libraries have been widely used to map the ligand specificity of proteins, to determine the substrate specificity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A neat chemical alternative to the generation and screening of bicylic peptides by phage display is to use the one-bead-two-compound (OBTC) approach, as illustrated by Pei and colleagues . The advantage of OBTC compared to biological display methods is the control over structural diversity: in fact the one-bead-one-compound approach also works well for the generation and screening of nonpeptidic or peptidemimetic compound libraries. Where OBTC falls down though (and where phage display really excels) is in the evolutionary optimization of active compounds. Nevertheless, the OBTC approach has been applied with success to identify potent inhibitors of Tumor Necrosis Factor-α (TNF-α), for instance Anticachexin C1 ( 53 , Figure ).…”
Section: Approaches For Hit Identification Of Ppi Modulatorsmentioning
confidence: 99%
“…A neat chemical alternative to the generation and screening of bicylic peptides by phage display is to use the one-bead-two-compound (OBTC) approach, as illustrated by Pei and colleagues . The advantage of OBTC compared to biological display methods is the control over structural diversity: in fact the one-bead-one-compound approach also works well for the generation and screening of nonpeptidic or peptidemimetic compound libraries. Where OBTC falls down though (and where phage display really excels) is in the evolutionary optimization of active compounds. Nevertheless, the OBTC approach has been applied with success to identify potent inhibitors of Tumor Necrosis Factor-α (TNF-α), for instance Anticachexin C1 ( 53 , Figure ).…”
Section: Approaches For Hit Identification Of Ppi Modulatorsmentioning
confidence: 99%
“…The screening of an OBOC library often requires a secondary protein that is labeled with a fluorophore or enzyme. For example, secondary antibodies [5] or streptavidin for staining biotinylated proteins have been used [32]. In these cases, false positive peptides might be identified that show affinity to the secondary reagent and not to the target protein.…”
Section: Resultsmentioning
confidence: 99%
“…To unbiasedly find a dipeptide nucleophile that efficiently induces transpeptidation, we designed a method using one-bead-one-compound (OBOC) peptide libraries ( Figure 3 ) [ 20 , 21 , 22 ]. The OBOC libraries were composed of beads carrying various peptides in which the N-terminal’s two amino acids (the X 1 and X 2 positions from N-terminus) were randomized and followed by a linker sequence AAARM in which the three alanines, one arginine, and the C-terminal methionine were used for the longer length, solubility and better detection in MALDI, and the cyanogen bromide (CNBr)-induced cleavage of attached peptides, respectively.…”
Section: Resultsmentioning
confidence: 99%